(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
The purpose of this concept paper is to provide a set of basic ethical principles that define the professional responsibilities of university professors in their role as teacher. Ethical principles are conceptualized here as general guidelines, ideals or expectations that need to be considered, along with other relevant conditions and circumstances, in the design and analysis of university teaching. This study extends current literature by distinguishing between moral/ethical and legal/ethical matters and then re-evaluating the effectiveness of ethics training. A cohort of academics with significant ethical training evaluated ethical scenarios. Half were moral and half contained legal as well as moral components. After further ethical instruction they re-evaluated the scenarios. Ethical attitudes towards legal/moral issues improved, but attitudes towards moral- only issues did not. Are fundamental ethical principles being ignored in an effort to prevent more obvious accounting wrongdoings? Accounting ethics training needs to be reassessed if true ethical improvement is to be achieved. Keywords: Ethical principles, Teaching, University 1 Department of Unani, Institute of Indigenous Medicine, University of Colombo, Colombo, Sri Lanka. 2 Faculty of Technology, South Eastern University of Sri Lanka, Oluvil, Sri Lanka. 3General Sir John Kotelawala Defense University, Ratmalana. Sri Lanka. 4 Faculty of Health Science, The Open University of Sri Lanka, Nawala, Sri Lanka. *Correspondence: Faiz MMT Marikar, General Sir John Kotelawala Defense University, Ratmalana. Sri Lanka. Email: faiz.marikar@fulbrightmail.org